Does Margin Call Pressure Affect the M&A Decision of Controlling Shareholders With Equity Pledges: Evidence From Chinese Listed Company - Li, Xintao; Li, Qian (Frontiers in Psychology, 2022)
The equity pledge has become a universal practice in the world. Taking Chinese listed companies from 2007 to 2020 as a sample, this paper investigates the influence of controlling shareholders’ equity pledges on M&A behavior. It is found that the probability of M&A of listed companies is greater when the controlling shareholder has an equity pledge (or the proportion of equity pledge of controlling shareholder is higher). M&A activities can raise the stock price and play the role of market value management. Controlling shareholders with margin call pressure have stronger motivation to use M&A to increase their share price. Investors seem to be aware of this behavior and underestimate the potential benefits of M&A under this pressure. Propensity score matching (PSM) and difference in difference (DID) were used to test endogeneity and the results were still robust. Overall, our results reveal the impact of equity pledges by controlling shareholders on M&A. Furthermore, margin call pressure, this organizational psychology promotes this possibility.